Public Relations in Improving the Quality of Education - Melia Putri Utami; Rahmat Fikri; Bradley Setiyadi (Universitas Muhammadiyah Enrekang, 2024)
The aim of this research is to determine community relationships in improving the quality ofeducation. The methodology of this research is library research. Obtaining information or datafrom the library and using it as a basis for study is the goal of library research. The results ofthis research show that public relations is an organization's reputation management strategyto determine public views and inform the public about how good public relations are inimproving the quality of education. In line with recent educational advances, educationalpublic relations professionals working with communities consider and seek to improve thequality of educational activities. A pleasant school environment is always created so thatstudents can receive education according to their abilities, and improving teachers' skills or expertise in managing schools can help improve the quality of education and ensure that theteaching given to students can be well absorbed.